From the strikes for the 8-hour workday to the Social Reform. Forging change: the wood workers 1890-1943. - Mora Ramírez, Andrés (2025)
In recent years, Costa Rican society has seen an accelerated process of neoliberal counter-reform driven by an alliance between old and new groups of political power (some of which even appeal to a progressive discourse) and economic power, which have focused their actions on eroding and weakening the labor rights won several decades ago by organized workers’ movements. In this scenario, the most recent book by Dr. Francisco Rojas Sandoval invites us to delve into our history to find there elements that allow us to think critically about the challenges of the present, and not to give up the construction of possible futures. From the strikes for the 8-hour workday to the Social Reform. Forging change: the wood workers 1890-1943. Alajuela, C.R.: Editorial UTN. ISBN: 978-9968-629-61-4.